Culling structured hosts to eradicate vector-borne diseases - Hu, Xinli; Liu, Yansheng; Wu, Jianhong (Mathematical biosciences and engineering : MBE, 2009)
A compartmental model is developed, in the form of a nonautonomous system of delay differential equations subject to impulses at specific times, for mosquito-born disease control involving larvicides and insecticide sprays. Sufficient conditions in terms of the frequencies and rates of larvicides and insecticide sprays are derived, and numerical simulations are provided to illustrate the sharpness of these disease eradication conditions.